2013
DOI: 10.1158/1078-0432.ccr-13-0980
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Abcc4-Mediated Gastric Transport to the Absorption and Efficacy of Dasatinib

Abstract: Purpose Several oral multikinase inhibitors are known to interact in vitro with the human ATP-binding cassette transporter ABCC4 (MRP4), but the in vivo relevance of this interaction remains poorly understood. We hypothesized that host ABCC4 activity may influence the pharmacokinetic profile of dasatinib and subsequently affect its antitumor properties. Experimental Design Transport of dasatinib was studied in cells transfected with human ABCC4 or the ortholog mouse transporter, Abcc4. Pharmacokinetic studie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 51 publications
2
39
0
Order By: Relevance
“…We show that pretreatment with dasatinib, which inhibits SFKs and c-Abl, is sufficient to suppress activation and nuclear translocation of PKC␦. Further, a 20-mg/kg dose in our mouse model equates to a serum concentration that is easily obtained in patient populations (44,45). Expectedly, pretreatment with the c-Abl-selective inhibitor imatinib also blocked nuclear translocation, as evidenced by reduced binding of importin-␣ to PKC␦ following H 2 O 2 treatment.…”
Section: Discussionmentioning
confidence: 89%
“…We show that pretreatment with dasatinib, which inhibits SFKs and c-Abl, is sufficient to suppress activation and nuclear translocation of PKC␦. Further, a 20-mg/kg dose in our mouse model equates to a serum concentration that is easily obtained in patient populations (44,45). Expectedly, pretreatment with the c-Abl-selective inhibitor imatinib also blocked nuclear translocation, as evidenced by reduced binding of importin-␣ to PKC␦ following H 2 O 2 treatment.…”
Section: Discussionmentioning
confidence: 89%
“…In addition, ABCG2 and ABCC4 have some similar substrates (44). Among the ABCC4 substrates tested in the tumorspheres were an antifolate (methotrexate), (19) KI (dasatinib) (45), and camptothecin (topotecan). Topotecan is readily transported by human and murine ABCC4 (19), thus, it is conceivable that a dual inhibitor, producing combined inhibition of both ABCC4 and ABCG2, might yield greater overall improvements in survival.…”
Section: Discussionmentioning
confidence: 99%
“…For example, previous studies have shown that the Mrp4 substrate, dasatinib, exhibits poor oral absorption in the absence of Mrp4, due to its high expression in the stomach. [28] We postulate that decreased mercaptopurine absorption from the stomach of Mrp4 knockout mice could account for relatively greater tolerance in Mrp4 KO mice compared to TPMT KO mice.…”
Section: Discussionmentioning
confidence: 99%